Hyperandrogenism in a Postmenopausal Woman Secondary to Testosterone Secreting Ovarian Stromal Tumor with Acoustic Schwannoma. (5th December 2018) - Gandrapu, Bindu; Sundar, Preeyanka; Phillips, Brian
Abstract : Androgen-secreting ovarian neoplasms are rare ovarian tumors that present with hirsutism and virilization which may manifest as severe alopecia, deepening of voice, and clitoromegaly. Most often, ovarian tumors are found to be very small or even undetectable. In such cases, bilateral salpingo-oophorectomy should be performed after ruling out other causes of high androgens. We present a 63-year-old postmenopausal woman with clinically and radiologically undetectable testosterone-secreting ovarian tumor, which was later on detected on biopsy.